1994
DOI: 10.1111/j.1365-2044.1994.tb04464.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of simple identification tests to distinguish cerebrospinal fluid from local anaesthetic solution

Abstract: SummaryLocal anaesthetic solution is sometimes used to enlarge the epidural space in preparation for the insertion of an indwelling epidural catheter and during subsequent checking a small volume of fluid may be aspirated. Twelve anaesthetists were asked to distinguish 0.1 ml plain bupivacaine 0.25% from 0.1 ml simulated cerebrospinalfluid (CSF) solution. The distinction was based on differences in the physicochemical properties of the two test solutions, namely, temperature, presence of glucose, pH, and turbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The volume of saline collected was not standardized, and this may be considered a study limitation since the volume injected may influence the volume leaking out. However, our observational study, unlike previous studies, 11,12 was designed to reflect clinical practice and therefore optimise external validity. The two dural punctures that occurred in the study were clinically obvious.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The volume of saline collected was not standardized, and this may be considered a study limitation since the volume injected may influence the volume leaking out. However, our observational study, unlike previous studies, 11,12 was designed to reflect clinical practice and therefore optimise external validity. The two dural punctures that occurred in the study were clinically obvious.…”
Section: Discussionmentioning
confidence: 92%
“…Studies by Walker and Brock-Utne 11 and Tessler et al 12 indicated that a sample size of 40 patients in each group would be suitable for an observational study. Data are presented using descriptive statistics and Kruskal-Wallis equality-of-populations rank test for testing differences between CSF and epidural fluid glucose for both glucometer and laboratory readings.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations